REPRESENTASI PENGGUNAAN MEDIA SOSIAL DALAM FILM THE SOCIAL DILEMMA (KAJIAN SEMIOTIKA JOHN FISKE) - Muhammad Farchan Febrianto (2021)
This study aims to find out the semiotic meaning of the use of social media in the film The Social Dilemma, as well as to analyze the signs contained in the film The Social Dilemma related to the use of social media from the level of reality, the level of representation, and the level of ideology. This study uses a constructivist paradigm, with a descriptive qualitative approach, and John Fiske's semiotic analysis method. The objects analyzed in this study consist of interview transcripts contained in the film The Social Dilemma which are divided into six categories: the impact of social media, business models, artificial intelligence, persuasive technology, dissemination of information on social media, and ways of responding to the use of social media. The results of the study show that the film The Social Dilemma represents the negative impact of social media, which is explained from the statements of the informants about social media technology, as well as the reenactment. This film also carries the ideology of capitalism as seen from the business model that applies in the social media technology industry, such as looking for profit from disinformation because it gives companies a lot of money.